2003
DOI: 10.1021/ac0205964
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pressure on the Retention and Separation of Insulin Variants under Linear Conditions

Abstract: The effect of pressure on the retention behavior of insulin variants in RPLC on a YMC-ODS C18 column was investigated under linear conditions. The retention factors of these variants increase nearly 2-fold when the average column pressure is increased from 55 to 250 bar while their separation factors remain nearly unchanged. This effect is explained by a change of the partial molar volume of the insulin variants associated with their adsorption that decreases from -99 to -80 mL/mol for mobile-phase concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 69 publications
2
25
1
Order By: Relevance
“…In contrast, the increase in retention factor for ribonuclease A was a factor of 1.3 with double the flow rate/pressure. This effect has previously been reported [19]. …”
Section: Resultssupporting
confidence: 85%
“…In contrast, the increase in retention factor for ribonuclease A was a factor of 1.3 with double the flow rate/pressure. This effect has previously been reported [19]. …”
Section: Resultssupporting
confidence: 85%
“…For large molecules such as proteins, it has been observed that pressure can have a rather strong influence on retention [207][208][209][210][211]. The change of retention can be attributed to the fact that the partial molar volume of the analyte is smaller when it is adsorbed in the stationary phase than when it is in the liquid mobile phase [207][208][209][210][211].…”
Section: Effect Of Pressurementioning
confidence: 99%
“…The change of retention can be attributed to the fact that the partial molar volume of the analyte is smaller when it is adsorbed in the stationary phase than when it is in the liquid mobile phase [207][208][209][210][211]. The conformational change (unfolding or spreading) of a protein molecule upon adsorption is a well-known phenomenon that leads to the exposure of its hydrophobic core [209,210]. At higher pressures, the adsorption of proteins onto the stationary phase is thus more relevant.…”
Section: Effect Of Pressurementioning
confidence: 99%
“…However, if this approach allows an easy separation of proteins, such separations can be modeled only if the isotherm data can be measured accurately, which supposes the possibility to perform their isocratic elution (7). A variety of interferences can be observed, e.g., protein aggregation (8), protein unfolding (9), and isomerization, which prevent the achievement of satisfactory results. Finally, the retention of proteins depends much more on the pressure than that of low molecular weight compounds ( 9 − 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we report on the modeling of the chromatographic behavior of an insulin variant, Lispro, on a conventional packed C 18 ‐bonded silica column, using an acidic solution of acetonitrile in water as the mobile phase. Under the experimental conditions selected for this work, there are no adverse effects due to insulin aggregation (9) while the presence of internal −S−S− bridges blocks the molecule under a globular structure that offers restricted possibility of isomerization. Although it is small (MW = 5808), insulin has a behavior that can be considered as representative of that of many proteins.…”
Section: Introductionmentioning
confidence: 99%